Assessment of community health volunteers' knowledge on cervical cancer in Kadibo Division, Kisumu County: a cross sectional survey - Edwin Onyango Ochomo; Harrysone Atieli; Sussy Gumo; Collins Ouma (BMC, 2017)
Abstract Background Globally, cervical cancer is the fourth most frequent cancer in women, with an estimated 530,000 new cases in 2012, representing 7.5% of all female cancer deaths. Of the estimated more than 270,000 deaths from cervical cancer every year, more than 85% occur in less developed regions. In sub-Saharan Africa, 34.8 new cases of cervical cancer are diagnosed per 100,000 women annually, and 22.5/100,000 women die from the disease. Despite the magnitude of this problem, Kenya still has a screening rate of 3.2%; therefore, cervical cancer prevalence has not been established. Community Health Volunteers (CHV) are required to create demand for screening in the community and capture this in the Ministry of Health (MOH) reporting tool MOH 514. The objective of this study was to determine the knowledge of risk factors, signs and symptoms of cervical cancer and screening services' availability amongst CHVs to enable them sensitize the community about cervical cancer in Kadibo Division, Kisumu County. Method In a cross-sectional study, a saturated sample of 188 CHVs was interviewed. The knowledge of cervical cancer was presented by use of frequencies and proportions; the relationship between demographic characteristics and knowledge was determined using chi-square. Results A majority, 161 (85.6%), were women, 47 (25.0%) were aged 40-44, 91 (48.4%) had primary education and 132 (70.2%) were small-scale farmers. A total of 128 (68.1%) had low, 60 (31.9%) had average and none had high amount of knowledge of risk factors. On average, 95 (50.5%) had low, 15 (8.0%) had average and 78 (41.5%) had high amount of knowledge of signs and symptoms. Finally, 77 (41.0%) had high, 40 (21.2%) had average and 71 (37.8%) had low knowledge of the availability of screening services. Education (p = 0.012, χ2 = 3.839), occupation (p < 0.0001, χ2 = 12.722), and health centre of attachment (p < 0.0001, χ2 = 71.013) were significant factors in determining the knowledge of risk factors. The knowledge of the signs and symptoms of cervical cancer was determined by the occupation of the CHVs (p = 0.030, χ2 = 15.110) and the years of work as a CHV (p = 0.014, χ2 = 8.451). Finally, the education level (p = 0.011, χ2 = 8.605), occupation (p = 0.002, χ2 = 18.335) and health centre of attachment (p < 0.0001, χ2 = 101.705) were significant in determining the knowledge of availability of screening services at the various health facilities. Conclusion The following were found to significantly influence the knowledge of CHVs about cervical cancer: level of education, occupation, health facility of attachment and years of service as a CHV. There is need, therefore, for training on cervical cancer.